2021
DOI: 10.3390/jcm10194461
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Ultrasound Assessment of Skin and Oral Mucosa in Metabolic Syndrome Patients—A Cross-Sectional Study

Abstract: Background: Exogenous factors (such as sun exposure, smoking habits, and diet) and endogenous (inflammatory status, general diseases) have a direct influence on skin and soft tissue characteristics. The study’s objective was to assess the impact of metabolic syndrome (MS) on characteristics of skin layers in sun-exposed and non-exposed maxillofacial tissues evaluated by high-frequency ultrasound (HFU), as a potential diagnosis and monitoring tool for the aging process. Material and methods: The present study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…This result is consistent with that of histological sections acquired from skin flap tissues excised on day 7 post-surgery, as given in Figure 13 , where the thickness of skin flap of different parts is estimated to be 3.17, 2.64, and 2.01 mm accordingly. Dehydration and collagen denaturation in the dermis of skin flap in accordance with the progress of necrosis may lead to the higher density of collagen fibers and the shrinkage of the extracellular matrix (ECM) [ 17 ], as can be seen in Figure 13 . Moreover, immune cells may be observed in the middle part of skin flap, as marked by the yellow arrows in Figure 13 , and correspond to more inflammatory response than the tissues of other regions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is consistent with that of histological sections acquired from skin flap tissues excised on day 7 post-surgery, as given in Figure 13 , where the thickness of skin flap of different parts is estimated to be 3.17, 2.64, and 2.01 mm accordingly. Dehydration and collagen denaturation in the dermis of skin flap in accordance with the progress of necrosis may lead to the higher density of collagen fibers and the shrinkage of the extracellular matrix (ECM) [ 17 ], as can be seen in Figure 13 . Moreover, immune cells may be observed in the middle part of skin flap, as marked by the yellow arrows in Figure 13 , and correspond to more inflammatory response than the tissues of other regions.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that 50 MHz high-frequency ultrasound (HFUS) imaging has a promising image resolution of up to 40 μm, capable of differentiating layers of tissue structures, including forearm, cheek, eye corner [ 13 ]. HFUS has also demonstrated the ability to diagnose inflammation responses [ 14 , 15 ] as considered for providing better treatment and care for an increase in skin flap survival as well as to characterize the skin tissue properties and severity of the cutaneous diseases in situ [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%